How the design and implementation of centralized waiting lists influence their use and effect on access to healthcare - A realist review. Issue 8 (August 2020) - Breton, Mylaine; Smithman, Mélanie Ann; Sasseville, Martin; Kreindler, Sara A.; Sutherland, Jason M.; Beauséjour, Marie; Green, Michael; Marshall, Emily Gard; Jbilou, Jalila; Shaw, Jay; Brousselle, Astrid; Contandriopoulos, Damien; et al.
Highlights: Centralized waiting lists (CWLs) aim to improve access by managing the asymmetry between supply and demand for a service. CWLs place patients into a queue and assign patients to the next available service from a pool of participating providers. CWLs use and effectiveness depend on provider behaviours at multiple stages in the CWL process. CWL design should consider acceptability, adherence, familiarity, perceived appropriateness and motivation mechanisms. Disregarding these behaviours in designing and implementing CWLs may limit effects on access or lead to inequities. Abstract: Context: Many health systems have centralized waiting lists (CWLs), but there is limited evidence on CWL effectiveness and how to design and implement them. Aim: To understand how CWLs' design and implementation influence their use and effect on access to healthcare. Methods: We conducted a realist review (n = 21 articles), extracting context-intervention-mechanism-outcome configurations to identify demi-regularities (i.e., recurring patterns of how CWLs work). Results: In implementing non-mandatory CWLs, acceptability to providers influences their uptake of the CWL. CWL eligibility criteria that are unclear or conflict with providers' role or judgement may result in inequities in patient registration. In CWLs that prioritize patients, providers must perceive the criteria as clear and appropriate to assess patients' level of need; otherwise, prioritization may be inconsistent. During patients' assignment to service providers, providers may select less-complex patients to obtain CWLs rewards or avoid penalties; or may select patients for other policies with stronger incentives, disregarding the established patient order and leading to inequities and limited effectiveness. Conclusion: These findings highlight the need to consider provider behaviours in the four sequential CWL design components: CWL implementation, patient registration, patient prioritization and patient assignment to providers. Otherwise, CWLs may result in limited effects on access or lead to inequities in access to services.